2002
DOI: 10.1097/00005392-200207000-00103
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Erectile Function after Brief Aggressive Antihypertensive Therapy

Abstract: The improvement in erectile function after brief aggressive treatment may be related to improvement in structurally based vascular resistance within the penis and the decrease in responsiveness of alpha1-adrenoceptor mediated erectolytic signaling. These findings are suggestive of a new therapeutic strategy for hypertension and erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 31 publications
3
38
0
2
Order By: Relevance
“…40 Rho kinase has further been shown to have a role in hypertension and its expression correlates to aging, which provides a partial explanation not only for the relationship between LUTS and ED, but also for the connection of LUTS, ED and hypertension. 41 Pelvic atherosclerosis An additional mechanism is diffuse atherosclerosis of blood vessels supplying prostate, penis and bladder. 42 In a recent epidemiologic study that supports this notion, both men and women who had two risk factors of atherosclerosis (diabetes mellitus, hypertension, hyperlipidemia and nicotine use) had a statistically significant higher IPSS compared with subjects with one or no risk factors.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…40 Rho kinase has further been shown to have a role in hypertension and its expression correlates to aging, which provides a partial explanation not only for the relationship between LUTS and ED, but also for the connection of LUTS, ED and hypertension. 41 Pelvic atherosclerosis An additional mechanism is diffuse atherosclerosis of blood vessels supplying prostate, penis and bladder. 42 In a recent epidemiologic study that supports this notion, both men and women who had two risk factors of atherosclerosis (diabetes mellitus, hypertension, hyperlipidemia and nicotine use) had a statistically significant higher IPSS compared with subjects with one or no risk factors.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…[1][2][3][4] These effects have been shown in several models of experimental hypertension, including the Prague hypertensive rat 5 and the genetically hypertensive rat, 6,7 although this is best documented in the spontaneously hypertensive rat (SHR). [1][2][3]8,9 The concept that the persistent reduction in MAP and the regression of vascular structure are linked mechanistically has also been widely discussed, although without resolution. 1-4,10 -14 Further, the vascular structural changes that persist off-treatment have been proposed to result from extended inhibition of the trophic actions of angiotensin II, 8,15,16 prolonged reduction in arterial pressure, 16 -18 or from the combined effects.…”
mentioning
confidence: 99%
“…18 Although treatment of hypertension with common antihypertensive medications has been associated with ED, 19,20 another study also showed recovery of erectile function after brief aggressive antihypertensive therapy. 21 Moreover, antihypertensives at levels currently used in clinical settings are not likely to negatively influence ED significantly. 22 Our results suggest that although it may be important to lower HbA1c levels below a clinically important threshold to experience improvement in ED, any reduction in BP may also provide beneficial effects.…”
Section: Discussionmentioning
confidence: 99%